Buying considerations of selected UP runners regarding shoes used for running - Villanueva, Michael C. (College of Home Economics, University of the Philippines Diliman, 2011)
This study aimed to determine the different factors that influence a runner's preference when buying shoes to be used for running and then find out the order of importance of these factors as perceived by the respondents. To achieve this, the research needed to profile the different needs of runners in terms of shoes, determine how demographics relate to shoe preference and lastly, determine how practicality, aesthetics and psychosocial factors rate in with the participants' preferences. The data was gathered through the survey method conducted among 40 respondents selected purposively among individuals jogging, running or cooling around U.P. Diliman Academic Oval using a random convenience sampling method. The questionnaire included questions on demographic data and took quantitative information with the help of a modified Likert scale. The study determined that proper support and cushioning and the correct show type for each necessary foot type and gait were considered very important when choosing shoes for running. Improper or inadequate shoes could cause and or aggravate injuries. The results showed that Practical factors were the leading priority of the ample population. followed by Aesthetic factors and the rounded off by Psychosocial factors. Since there was not a big margin in terms of difference in points, we can safely say that we cannot discount the significance of Psychosocial factors even if it came in last at the tally. As a recommendation for further study, perhaps the study could be repeated with a larger sample set so as to enable the use of more advanced statistical methods for results interpretation.